Comfortcozy handsock / Ainnur Insyirah Mazlan … [et al.]. - Mazlan, Ainnur Insyirah; Badrulhissham, Diyana Fatimah; Nor Hasyimi, Nurul Aina Syamimi; Azmi, Nurul Asyiqin; Abd Rashid, Qasdina Amirah (2024)
Brief description of the business and product concepts: The main purpose behind the development of ComfortCozy Handsock is to introduce an innovative technology handsock suitable not only for women but also for men, athletes, delivery workers, and more. Crafted from high-quality nylon spandex, ComfortCozy Handsock offers enhanced comfort with its lightweight material, gentle on the skin. Additionally, it features adjustable buttons to cater to customers’ preferences. Other than that, our products are guaranteed to be of high quality, and it is very affordable. ComfortCozy Handsock is suitable for those who are looking for a handsock that is adjustable and friendly to the skin, and most importantly, comfortable when wearing it. The target market and projection. Initially, our focus was on Muslim women who wear handsocks to cover their arms. However, our research revealed that the demand for handsocks transcends gender and extends to individuals in various fields, such as construction, delivery, and athletics, driven by reasons such as sun protection or job-specific requirements. We assure users that they will find ComfortCozy Handsocks enjoyable due to their comfort, non-irritating nature, breathability, and quick sweat-drying features.